Nephrotoxicity after radionuclide therapies - Ashwin Singh Parihar (Elsevier, 2022)
Radioligand therapies have opened new treatment avenues for cancer patients. They offer precise tumor targeting with a favorable efficacy-to-toxicity profile. Specifically, the kidneys, once regarded as the critical organ for radiation toxicity, also show excellent tolerance to radiation doses as high as 50–60 Gy in selected cases. However, the number of nephrons that form the structural and functional units of the kidney is determined before birth and is fixed. Thus, loss of nephrons secondary to any injury may lead to an irreversible decline in renal function over time. Our primary understanding of radiation-induced nephropathy is derived from the effects of external beam radiation on the renal tissue. With the growing adoption of radionuclide therapies, considerable evidence has been gained with regard to the occurrence of renal toxicity and its associated risk factors. In this review, we discuss the radionuclide therapies associated with the risk of nephrotoxicity, the present understanding of the factors and mechanisms that contribute to renal injury, and the current and potential methods for preventing, identifying, and managing nephrotoxicity, specifically acute onset nephropathies.